A comprehensive overview of exosome lncRNAs: emerging biomarkers and potential therapeutics in endometriosis - Wang, Min; Zheng, Lianwen; Lin, Ruixin; Ma, Shuai; Li, Jiahui; Yang, Shuli (Frontiers in Endocrinology, 2023)
Endometriosis (EMs) is a gynecological condition that has a significant impact on women's daily lives. In recent years, the incidence of EMs has been rising yearly and is now an essential contributor to female infertility. Exosomes are a type of extracellular vesicles (EVs) that not only carry long noncoding RNA (lncRNA) but also shield lncRNA from the outside environment thanks to their vesicle-like structure. The role of exosome-derived lncRNAs in EMs is also receiving more study as high-throughput sequencing technology develops. Several lncRNAs with variable expression may be crucial to the emergence and growth of EMs. The early diagnosis of EMs will be considerably improved by further high specificity and sensitivity Exosome lncRNA screening. Exosomes assist lncRNAs in carrying out their roles, offering a new target for the creation of EM-specific medications. In order to serve as a reference for clinical research on the pathogenesis, diagnosis, and treatment options of EMs, this paper covers the role of exosome lncRNAs in EMs and related molecular mechanisms.